Hubungan Dukungan Pemerintah Sektor Pariwisata Terhadap Tingkat Inklusivitas Ekonomi di Daerah - Rattekarua, Lucky Mutiara Pindan; Hartono, Djoni (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2023)
Economic development that creates broad access and opportunities for all segments of society, fosters equitable prosperity, and reduces disparities between groups and regions has been a global challenge up to today. The lack of an inclusive economy leads to higher inequality in regions, specifically for underprivileged communities in underdeveloped regions. In line with this, the government has encouraged the development of new tourism to boost economic growth aiming to reduce regional development disparities. However, empirical studies that prove the relationship between tourism and economic inclusiveness still need to be completed due to limited data in measuring economic inclusiveness. Using the Inclusive Development Index with panel data regression from 514 districts in Indonesia from 2016 to 2019, it is expected that this study will contribute to the literature, primarily related to inclusive tourism development. This study detected that government spending has a significant but adverse relationship with the level of economic inclusivity in the regions.